CatDog. Season 2, part 2 [videorecording (DVD)] - Cummings, Jim, 1952-; Kenny, Tom, 1962-; Porter, Robert (Shout! Factory, 2012)
A brand new set of crazy CatDog adventures! They're the craziest set of conjoined twins you'll ever meet: The culturally refined Cat, and Dog, who's not so much. Together, CatDog make it all work by both using and strengthening their own friendship, providing their own excitement and even getting into their own heap of hilarious trouble! Includes episodes eleven through 20 of season two.